Animals and Inequality in the Ancient World - Arbuckle, Benjamin S.; McCarty, Sue Ann (University Press of Colorado, 2015)
Animals and Inequality in the Ancient World explores the current trends in the social archaeology of human-animal relationships, focusing on the ways in which animals are used to structure, create, support, and even deconstruct social inequalities. The authors provide a global range of case studies from both New and Old World archaeology-royal Aztec dog burial, the monumental horse tombs of Central Asia, and the ceremonial macaw cages of ancient Mexico among them. They explore the complex relationships between people and animals in social, economic, political, and ritual contexts, incorporating animal remains from archaeological sites with artifacts, texts, and iconography to develop their interpretations. Animals and Inequality in the Ancient World presents new data and interpretations that reveal the role of animals, their products, and their symbolism in structuring social inequalities in the ancient world. The volume will be of interest to archaeologists, especially zooarchaeologists, and classical scholars of pre-modern civilizations and societies. Contributors: Alejandra Aguirre Molina, Benjamin S. Arbuckle, Levent Atici, Douglas V. Campana, Roderick Campbell, Ximena Chávez Balderas, Pam J. Crabtree, Susan D. deFrance, Kitty F. Emery, Abigail Holeman, H. Edwin Jackson, Leonardo López Luján, Michael MacKinnon, Arkadiusz Marciniak, Sue Ann McCarty, Neil L. Norman, Gilberto Perez, Bernardo Rodriguez, William A. Saturno, Ashley E. Sharpe, Nawa Sugiyama, Charlotte K. Sunseri, Naomi Sykes, Fabiola Torres, Raul Valadez, Norma Valentin Maldonado, Adam S. Watson, Joshua Wright, Belem Zuniga-Arelleno